The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-12268-9
|View full text |Cite
|
Sign up to set email alerts
|

Viral outbreaks involve destabilized evolutionary networks: evidence from Ebola, Influenza and Zika

Abstract: Recent history has provided us with one pandemic (Influenza A/H1N1) and two severe viral outbreaks (Ebola and Zika). In all three cases, post-hoc analyses have given us deep insights into what triggered these outbreaks, their timing, evolutionary dynamics, and phylogeography, but the genomic characteristics of outbreak viruses are still unclear. To address this outstanding question, we searched for a common denominator between these recent outbreaks, positing that the genome of outbreak viruses is in an unstab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…On this, though detection times may vary greatly in respect virus types (influenza, Henipavirus (Nipah virus), Filoviruses like Ebola, and Flavivirus like Zika et cetera) [16,17] and other characteristics, the constant is that technological advancement is clearly aiding in reducing their detection time. This was evidenced in the recent case of COVID-19, taking only seven days for detection.…”
Section: A Brief Survey On Infectious Disease Outbreak In a 20-year Pmentioning
confidence: 99%
“…On this, though detection times may vary greatly in respect virus types (influenza, Henipavirus (Nipah virus), Filoviruses like Ebola, and Flavivirus like Zika et cetera) [16,17] and other characteristics, the constant is that technological advancement is clearly aiding in reducing their detection time. This was evidenced in the recent case of COVID-19, taking only seven days for detection.…”
Section: A Brief Survey On Infectious Disease Outbreak In a 20-year Pmentioning
confidence: 99%
“…Note however that this latter analysis is more informative than the former, as the density also shows that most of the sites under selection are involved in weak interactions. This is intriguingly reminiscent of the involvement of weakly interacting pairs of sites in severe outbreaks or pandemics (Aris-Brosou et al ., 2017).…”
Section: Resultsmentioning
confidence: 92%
“…These reconstructed mutational paths were then recoded as a binary matrix, with rows corresponding to branches and columns to a site of the alignment. The BGM was then used to identify the pairs of sites that exhibit correlated patterns of nonsynonymous substitutions according to their posterior probability, estimated with a Markov chain Monte Carlo sampler that was run for 10 5 steps, with a burn-in period of 10,000 steps sampling every 1,000 steps for inference (Aris-Brosou et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, however, correlated evolution has only sporadically been investigated in viral evolution, and these rare instances only focused on ssRNA viruses. Indeed, recent work uncovered pervasive evidence for correlated evolution in influenza viruses [14,15], and both the Zika [16] and the Ebola viruses [17]. Intriguingly, in this latter case (Ebola), evidence was found that sites evolving in a correlated manner could also be under positive selection—bearing the question as to how frequently these two processes, correlated evolution and positive selection, occur, possibly jointly, and if this co-occurrence is limited to ssRNA viruses, or can be generalized to all viruses.…”
Section: Introductionmentioning
confidence: 99%